2022
DOI: 10.1007/s11482-021-10034-8
|View full text |Cite
|
Sign up to set email alerts
|

Using Autonomous Teams to Improve Quality of Life of People with Intellectual Disabilities

Abstract: This research study tested an intervention, based on autonomous teams and the service co-creation approach, to improve the social inclusion and self-determination (as indicators of quality of life) of people with intellectual disability. Members of the autonomous teams (professionals, people with intellectual disability, and family members) cooperated to plan and carry out a project. A total of 72 autonomous teams participated (experimental condition). Each team designed its action plan to be implemented durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…This research finding is different from the hypothesis of this study, and from previous theories and research findings that group interaction factors may improve the quality of life of individual employees by reducing stress levels at work. 81 , 82 What is the reason? From the perspective of the characteristics of the police organization, in police groups similar to military organizations, the efficiency in job execution and task completion are the most important aspects of police organizations.…”
Section: Discussionmentioning
confidence: 99%
“…This research finding is different from the hypothesis of this study, and from previous theories and research findings that group interaction factors may improve the quality of life of individual employees by reducing stress levels at work. 81 , 82 What is the reason? From the perspective of the characteristics of the police organization, in police groups similar to military organizations, the efficiency in job execution and task completion are the most important aspects of police organizations.…”
Section: Discussionmentioning
confidence: 99%
“…The previous research specifically examined the extent to which channels of participation and dialog between non‐disabled workers and family members are related to self‐determination and autonomy in persons with intellectual disabilities. The emphasis was mainly on generalizing the self‐determination of persons with intellectual disabilities to other contexts (e.g., family context) beyond the organization (Blížkovská et al, 2022; Martínez‐Tur et al, 2015) and achieving a shared vision (regarding the autonomy of persons with intellectual disabilities) between non‐disabled workers and family members (Martínez‐Tur et al, 2018). Overall, the results suggested that dialog and participation of family members in organizational life facilitate the generalization of self‐determination of persons with intellectual disabilities to other contexts, as well as attitudinal convergence between family members and non‐disabled workers toward self‐determination.…”
Section: Discussionmentioning
confidence: 99%
“…Sus beneficios primordiales abarcan la mejora del bienestar, el acceso a fuentes de ingresos, el estímulo al desarrollo personal e identitario y la creación de relaciones interpersonales (Friedman, 2017;Nogueira, 2022;Santuzzi & Waltz, 2016;Saunders & Nedelec, 2014). Por tanto, no disponer de un trabajo implica que las personas con discapacidad (en adelante, PcD) además de no tener una fuente de ingresos, ven afectada su participación en la sociedad, su autonomía, autodeterminación y, en consecuencia, su calidad de vida (Beart et al, 2005;Blížkovská et al, 2022;Scott & Havercamp, 2014). En consiguiente, las dificultades que experimentan las PcD y, específicamente las personas con SD, para incluirse en entornos laborales, se convierte en un desafío social que no puede ser ignorado.…”
Section: Introductionunclassified